Nursing in a postemotional society - Herdman, Elizabeth A. (Nursing philosophy, 2004)
Globalization is often seen as the final stage in the transition towards a market economy. It is argued that a side-effect of globalization is cultural homogeneity and loss of life world, or ‘McDonaldization’. McDonaldization represents the rationalization of society in the quest for extreme efficiency. More recently, Meštrović has argued that the rationalization of emotions has also occurred and that Western societies are entering a postemotional phase. In postemotional societies there has been a separation of emotion from action. The result is synthetic, manufactured emotions manipulated and standardized for mass consumption. In this paper I explore what it means to nurse in a ‘postemotional society’ and what impact this dulling of the emotions has had on a profession that locates ‘care’ as its central defining concept. My aim is to generate critical discussion of the shape and direction of contemporary society and the role of nursing within it.